2010
DOI: 10.2189/asqu.2010.55.4.543
|View full text |Cite
|
Sign up to set email alerts
|

The Paradox of Meritocracy in Organizations

Abstract: In this article, we develop and empirically test the theoretical argument that when an organizational culture promotes meritocracy (compared with when it does not), managers in that organization may ironically show greater bias in favor of men over equally performing women in translating employee performance evaluations into rewards and other key career outcomes; we call this the “paradox of meritocracy.” To assess this effect, we conducted three experiments with a total of 445 participants with managerial exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
445
0
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 558 publications
(475 citation statements)
references
References 82 publications
(144 reference statements)
19
445
0
11
Order By: Relevance
“…Another study (Castilla 2010) showed that Bbias can be triggered by attempts to reduce it, particularly in organizational contexts that emphasize meritocratic values.^This is to say, that organizations that explicitly tout meritocratic values, may end up committing more harm against the already disadvantaged, all the while, maintaining their belief that bonuses and raises are awarded on basis of hard work. 8 Here is a sample of one such encounter of a physician with a cancer-patient faced with their impending mortality: Patient: BI don't know what the average person does in 2 years, 3 years, a year?^Physician: BI think that … you certainly could live 2 or 3 years.…”
Section: Endnotesmentioning
confidence: 99%
“…Another study (Castilla 2010) showed that Bbias can be triggered by attempts to reduce it, particularly in organizational contexts that emphasize meritocratic values.^This is to say, that organizations that explicitly tout meritocratic values, may end up committing more harm against the already disadvantaged, all the while, maintaining their belief that bonuses and raises are awarded on basis of hard work. 8 Here is a sample of one such encounter of a physician with a cancer-patient faced with their impending mortality: Patient: BI don't know what the average person does in 2 years, 3 years, a year?^Physician: BI think that … you certainly could live 2 or 3 years.…”
Section: Endnotesmentioning
confidence: 99%
“…This has revealed that people tend to under-estimate rather than over-estimating the occurrence of group-level discrimination [30]. Additionally, the presence of representatives of undervalued groups [31], or of measures aiming to secure equal treatment, for instance in Modern discrimination 7 organizations, paradoxically makes us less vigilant against bias, and less likely to note discrimination when it occurs [32] …”
Section: Perceiving Discriminationmentioning
confidence: 99%
“…Much sociological and organizational theory (Reskin 2000;Reskin and Branch McBrier 2000;Bielby 2000;Reskin 2003;Dobbin 2009), supported by a growing body of empirical research (Huffman 1995;Kalev, Dobbin and Kelly 2006;Castilla 2008;Kalev 2009;Castilla and Benard 2010), suggests that it does. This work situates much employment discrimination not in the conscious actions of bigoted managers but in the unconscious impact of cognitive biases, deployed through personnel policies that fail to take such biases into account.…”
Section: Introductionmentioning
confidence: 99%
“…On balance, these studies find many of the theorized effects. It is not enough simply to tell people that their actions should be meritocratic (Castilla and Benard 2010), some best practices are better than others (Kalev et al 2006), and such policies seem stronger when there are outside parties who can hold policymakers accountable (Edelman 1992;Huffman 1995;Kalev et al 2006). These nuances notwithstanding, formal operating procedures that limit managers' discretion in hiring, retention and promotion seem to be associated with greater opportunities for women and ethnic minorities in firms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation